RECONSTRUCTION OF PRINCIPLES OF LEGALITY IN CRIMINAL LAW BASED ON JUSTICE VALUE OF PANCASILA - muhammad yahya selma (Jurnal Pembaharuan Hukum, 2017)
Amendment of the Constitution 1945 after the fourth amendment, reinforce the concept of the state law and put it in Article 1 paragraph 3 of the Constitution of the Republic of Indonesia in 1945 which reads : "The State of Indonesia is a state of law". The enactment of the provisions of Article 1 Paragraph (3) the Constitution of the Republic of Indonesia in 1945 brought a fundamental change to the principle of legality, which was previously law in Indonesia based on written law only, being based on written law and unwritten law or law that lives and grows in society. Law in Indonesia is based on the value of justice living in society based on the values of Pancasila.